The war after the war : the struggle for credibility during America's exit from Vietnam - Kadura, Johannes (Cornell University Press, 2016)
This book offers a fresh interpretation of American strategy in the wake of the cease-fire that began in Vietnam on January 28, 1973. The U.S. exit from Vietnam continues to be important in discussions of present-day U.S. foreign policy, so it is crucial that it be interpreted correctly. In challenging the prevailing version of the history of the events, the book provides interesting correctives to the different accounts, including the ones of the key actors themselves, President Richard Nixon and Secretary of State Henry Kissinger foremost among them.
Keywords: Vietnam War, 1961-1975 -- United States -- Public opinion.; Vietnam War, 1961-1975 -- United States.; HISTORY -- Asia -- Southeast Asia.; HISTORY -- United States -- 20th Century.; Public opinion; United States; 1961-1975